Global resilience and new strategies needed for antimicrobial stewardship during the COVID‐19 pandemic and beyond. Issue 7 (17th April 2022) - Goff, Debra A.; Gauthier, Timothy P.; Langford, Bradley J.; Prusakov, Pavel; Ubaka Chukwuemka, Michael; Nwomeh, Benedict C.; Yunis, Khalid A.; Saad, Therese; van den Bergh, Dena; Villegas, Maria Virginia; Martinez, Nela; Morris, Andrew; et al.
Abstract: Resilience is having the ability to respond to adversity proactively and resourcefully. The coronavirus disease 2019 (COVID‐19) pandemic's profound impact on antimicrobial stewardship programs (ASP) requires clinicians to call on their own resilience to manage the demands of the pandemic and the disruption of ASP activities. This article provides examples of ASP resilience from pharmacists and physicians from seven countries with different resources and approaches to ASP—The United States, The United Kingdom, Canada, Nigeria, Lebanon, South Africa, and Colombia. The lessons learned pertain to providing ASP clinical services in the context of a global pandemic, developing new ASP paradigms in the face of COVID‐19, leveraging technology to extend the reach of ASP, and conducting international collaborative ASP research remotely. This article serves as an example of how resilience and global collaboration is sustaining our ASPs by sharing new "how to" do antimicrobial stewardship practices during the COVID‐19 pandemic.